2021
DOI: 10.1177/00220345211004842
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Induced Changes in Salivary Gland Function and the Composition of Saliva

Abstract: Although the physiological control of salivary secretion has been well studied, the impact of disease on salivary gland function and how this changes the composition and function of saliva is less well understood and is considered in this review. Secretion of saliva is dependent upon nerve-mediated stimuli, which activate glandular fluid and protein secretory mechanisms. The volume of saliva secreted by salivary glands depends upon the frequency and intensity of nerve-mediated stimuli, which increase dramatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 66 publications
0
39
0
4
Order By: Relevance
“…Huang et al (2021) confirmed the expression of ACE2 and TMRPSS2 in oral mucosal epithelia and salivary glands, validating evidence of SARS-CoV-2 direct infection. Thus, the tropism of SARS-CoV-2 to the nervous system and these host factors expressed in serous and mucous salivary acini as well as taste buds may directly or indirectly result in saliva secretion dysfunction, xerostomia, and gustatory disorders (Herrera et al 2020;Pedrosa et al 2020;Huang et al 2021;Proctor and Shaalan 2021;Saniasiaya 2021;Tsuchiya 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2021) confirmed the expression of ACE2 and TMRPSS2 in oral mucosal epithelia and salivary glands, validating evidence of SARS-CoV-2 direct infection. Thus, the tropism of SARS-CoV-2 to the nervous system and these host factors expressed in serous and mucous salivary acini as well as taste buds may directly or indirectly result in saliva secretion dysfunction, xerostomia, and gustatory disorders (Herrera et al 2020;Pedrosa et al 2020;Huang et al 2021;Proctor and Shaalan 2021;Saniasiaya 2021;Tsuchiya 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies conducted in age-matched cohorts will be critical to confirm our findings and will provide a more complete understanding of salivary dysfuntion in the AD pathology as the mean age of control group is significantly lower than in AD patients. Salivary gland alterations and dysfunction, including the reduced glandular and acini volume, along with the loss of secretory volume, are associated with different diseases but also with aging (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern healthcare and access to various foods, periodontal diseases related to vitamin C deficiency are almost forgotten, but the ineffective removal of dental plaque in association with chronic stress, inveterate smoking, diabetes, dyslipidemia, etc., may result in periodontitis, which affects a large part of the population worldwide [ 2 , 5 , 6 , 7 , 8 ]. Rising life expectancy generates other problems such as tissue degeneration as well as neoplasms and their treatment, which may result in hyposalivation, immunodeficiency or malnutrition with subsequent oral diseases [ 9 , 10 , 11 , 12 ]. Proper oral hygiene is the basis of keeping the oral cavity healthy.…”
Section: Introductionmentioning
confidence: 99%